Legality and Conditions of Polygyny in Afghanistan Legal System - Ayoubi, Abdul Wahab; Ayoubi, Fazal Rahman (Integrated Journal for Research in Arts and Humanities, 2024)
Marriage, a cornerstone of social institution, is conventionally practiced through monogamy. However, Afghanistan presents an exception, permitting men to marriage in polygyny under specific conditions. The Afghan Civil Code delineates the framework for polygyny, emphasizing justifiable treatment of wives, financial capacity to support them(alimony), and the fulfillment of legitimate expediency. This research engages a descriptive research design and utilizes qualitative methods to gather data from primary and secondary library sources. The main objective of this study is to illuminate the legal framework and conditions governing polygyny in Afghanistan. The findings indicate that polygyny is not an illegitimate practice but is subject to stringent regulations. Incorporating spousal consent into these considerations could potentially mitigate future family conflicts.